Rehabilitation, Crime and Justice - Raynor, P. author. aut Link
VI, 204 p.
Keywords: Can offenders be rehabilitated? Can this be done in ways that benefit the community as a whole, as well as offenders? This book is about the history, theory, practice and effectiveness of rehabilitation. It shows how different beliefs about the value of rehabilitation and about 'what works' have influenced criminal justice policy and practice at different times, and it identifies a number of promising approaches for the future. Everyone interested in the rehabilitation of offenders should read this book.